Finanças, Economia e Instituições no Portugal Moderno (séculos XVI-XVIII) - Bruno Lopes (Investigação, 2019)
The present collection of unpublished studies intends to open new paths in the area of financial and economic history of Portugal, during the 16th-18th centuries. Gathering a set of young researchers from various specialties, we sought to offer a window to the past through ten cases of study that, from the metropolis to the Beyond-Sea, from the financial management of the institutions to the structuring of commercial networks, the economic importance of the landlords, the Municipal Councils, the Merlums and the Inquisition, allow us to understand the centrality of economic structures and the construction of the kingdom in the modern period.